2014
DOI: 10.1371/journal.pone.0096869
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Mitochondrial DNA Copy Number in Blood Is Not Associated with Major Depressive Disorder in Young Adults

Abstract: BackgroundMajor depressive disorder (MDD) is the leading cause of disability worldwide, and has significant genetic predisposition. Mitochondria may have a role in MDD and so mitochondrial DNA (mtDNA) has been suggested as a possible biomarker for this disease. We aimed to test whether the mtDNA copy number of peripheral blood leukocytes is related to MDD in young adults.MethodsA case-control study was conducted with 210 MDD patients and 217 healthy controls (HC). The mtDNA copy number was measured by quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
0
28
1
Order By: Relevance
“…Another study found impaired mitochondrial respiration in platelets of patients with depression (84, 85). With regard to mtDNA copy number, one study did not show alterations in 17–45 year-old Chinese outpatients with MDD compared with matched healthy controls (32). However, in a study of mtDNA copy number in community-dwelling Korean women over age 60, lower mtDNA copy numbers were seen in a subgroup on antidepressants or with high levels of depressive symptoms (33).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study found impaired mitochondrial respiration in platelets of patients with depression (84, 85). With regard to mtDNA copy number, one study did not show alterations in 17–45 year-old Chinese outpatients with MDD compared with matched healthy controls (32). However, in a study of mtDNA copy number in community-dwelling Korean women over age 60, lower mtDNA copy numbers were seen in a subgroup on antidepressants or with high levels of depressive symptoms (33).…”
Section: Discussionmentioning
confidence: 98%
“…mtDNA copy number has been reported to be high in autism (25), and reduced in a recent study of bipolar disorder (26) but not others (2731). A few studies have assessed mtDNA copy number in patients with MDD: no difference was found between MDD patients and controls in a small post-mortem study of brain tissue (31) or in a large study in outpatients with MDD and matched controls (32), but there is some evidence of reduced leukocyte mtDNA copy number in association with depression in women over age 60 (33). We are not aware of any investigations of mtDNA copy number in relation to anxiety disorders, alcohol or substance disorder, or psychosocial stress exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in community-dwelling women (n=142) found significantly lower mtDNAcn in people with higher depressive symptoms (not necessarily diagnosed with Major Depressive Disorder [MDD]) compared to those with lower depressive symptoms (Kim M. Y. et al 2011). However, one study found that mtDNAcn was not significantly different in subjects with MDD compared to controls (He Y. et al 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…The association between mtDNA and depression is inconsistent, with some studies reporting an increase in mtDNA among MDD cases, [3; 8] another reporting the opposite, [14] and another reporting no association; [15] the latter two studies had limited sample sizes. Few studies are available on clinical characteristics of MDD and their relationship with mtDNA, though Tyrka et al [8] , using a modest sample, reported no association between mtDNA copy number and depressive symptoms or perceived stress.…”
Section: Introductionmentioning
confidence: 99%